2019
DOI: 10.3390/languages4010016
|View full text |Cite
|
Sign up to set email alerts
|

Actions as a Basis for Online Embodied Concepts

Abstract: In co-speech gesture research, embodied cognition implies that concepts are associated with haptic and motor information that provides a framework for a gestural plan. When speakers access concepts, embodied action images are automatically activated. This study considers situations in which speakers need to create online concepts of events to investigate the aspect of the event that forms the basis of a new concept. Speakers watched short event video clips with familiar or unfamiliar attributes. They described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It has been suggested that when an abstract concept is metaphorically described in terms of a motion event, the motor system could play an essential role in processing that concept and grounding it in the physical environment . This is particularly the case when such a metaphorical description is supported by gestures that depict that motion event (e.g., Keily, 2019;Wellsby & Pexmann, 2019). When a literal sentence is used to describe an actual motion event in the physical environment or a metaphorical sentence is employed to metaphorically describe a specific concept (or event) in terms of a motion event, gestures can be used to give a visual description of that motion.…”
Section: Literal Change Vs Metaphorical Changementioning
confidence: 99%
“…It has been suggested that when an abstract concept is metaphorically described in terms of a motion event, the motor system could play an essential role in processing that concept and grounding it in the physical environment . This is particularly the case when such a metaphorical description is supported by gestures that depict that motion event (e.g., Keily, 2019;Wellsby & Pexmann, 2019). When a literal sentence is used to describe an actual motion event in the physical environment or a metaphorical sentence is employed to metaphorically describe a specific concept (or event) in terms of a motion event, gestures can be used to give a visual description of that motion.…”
Section: Literal Change Vs Metaphorical Changementioning
confidence: 99%